Extracellular 5′‐nucleotidase (CD73) promotes human breast cancer cells growth through AKT/GSK‐3β/β‐catenin/cyclinD1 signaling pathway. Issue 5 (31st October 2017) - Yu, Jiangang; Wang, Xue; Lu, Qi; Wang, Jigang; Li, Luying; Liao, Xiaohong; Zhu, Wei; Lv, Lei; Zhi, Xiuling; Yu, Jerry; Jin, Yiting; Zou, Qiang; et al.
Abstract : To identify the role and to explore the mechanism of extracellular 5′‐nucleotidase (CD73) in human breast cancer growth, CD73 expression was measured firstly in breast cancer tissues and cell lines, and then interfered with or over‐expressed by recombinant lentivirus in cell lines. Impacts of CD73 on breast cancer cell proliferation and cell cycle were investigated with colony formation assay, CCK‐8 and flow cytometry. The relationship between CD73 and AKT/GSK‐3β/β‐catenin pathway was assessed with adenosine, adenosine 2A receptor antagonist (SCH‐58261), adenosine 2A receptor agonist (NECA), CD73 enzyme inhibitor (APCP) and Akt inhibitor (MK‐2206). Moreover, the effect of CD73 on breast cancer growth in vivo was examined with human breast cancer transplanting model of nude mice. The results showed that the expression of CD73 was high in breast cancer tissues and increased with advanced tumor grades and lympho‐node status. CD73 expression was higher in more malignant cells, and CD73 overexpression promoted breast cancer cell proliferation in both in vivo and in vitro . It activated AKT/GSK‐3β/β‐catenin/cyclinD1 signaling pathway through CD73 enzyme activity and other mechanism. Abstract : What's new? The enzyme CD73 has been associated with tumor growth in many types of cancer, but investigations into its utility as a prognostic factor have produced mixed results. Here, the authors found high CD73 levels in breast cancer cells, and even higher in tumors with advanced stage. They found that boosting CD73 expression promoted cancer growth both in cell culture and in mouse models. Next, they showed that CD73 activated the AKT/GSK3beta/beta‐catenin signaling pathway, which spurs tumor growth. Therefore, the presence of CD73 could be an important prognostic tool for breast cancer.